The Quality of a Firm's Exports: Where You Export to Matters - Bastos, Paulo (2012)
What drives export quality? Using Portuguese firm-level data on exports by product and destination market, we find that f.o.b. unit values increase systematically with distance, and tend to be higher in shipments to richer nations. These relationships reflect not only the sorting of firms across markets, but also the within-firm variation of unit values across destinations. Within product categories, higher-productivity firms tend to ship greater quantities at higher prices to a given market, consistent with higher quality. In addition, firm productivity tends to magnify the positive effect of distance on within-product unit values, suggesting that high-productivity, high-quality firms are more able to serve difficult markets.